Role of Nd: YAG Laser in Visual Outcomes and IOP Changes pre and Post Nd: YAG Laser Capsulotomy (Global Journal of Medical Research, 2021)
Abstract not found
Keywords: Nd: YAG laser; posterior capsular opacification; visual acuity; intraocular pressure